2010
DOI: 10.1016/j.aca.2010.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of electrokinetic transport in silica nanofluidic channels

Abstract: We present a theoretical and numerical modeling study of the multiphysicochemical process in electrokinetic transport in silica nanochannels. The electrochemical boundary condition is solved by considering both the chemical equilibrium on solid-liquid interfaces and the salt concentration enrichment caused by the double layer interaction. The transport behavior is modeled numerically by solving the governing equations using the lattice Poisson-Boltzmann method. The framework is validated by good agreements wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 59 publications
(129 reference statements)
1
30
1
Order By: Relevance
“…Of particular interest is the intricate interplay among surface chemistry, electrokinetics, and fluid dynamics spanning over molecular and continuum macroscopic length scales [4,5]. It has been demonstrated that the electrokinetic properties at this scale have enabled a range of innovations including those for chemical sensing and bioanalytics [6][7][8][9][10][11][12], energy harvesting systems, [13][14][15][16][17][18], and nanofluidic ion transport [19][20][21][22][23][24][25][26], including enrichment, depletion, and rectification effects [27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Of particular interest is the intricate interplay among surface chemistry, electrokinetics, and fluid dynamics spanning over molecular and continuum macroscopic length scales [4,5]. It has been demonstrated that the electrokinetic properties at this scale have enabled a range of innovations including those for chemical sensing and bioanalytics [6][7][8][9][10][11][12], energy harvesting systems, [13][14][15][16][17][18], and nanofluidic ion transport [19][20][21][22][23][24][25][26], including enrichment, depletion, and rectification effects [27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to previous works focused mainly on full numerical simulations [5][6][7][11][12][13][14][16][17][18] or based on the Debye-Hückel approximation (low surface potential) [15], analytical expressions are derived for the first time to predict the streaming electric field (E str ), streaming current (I str ), and streaming conductance (S str ) taking into account the electroviscous and Stern layer effects, the presence of H + and OH − ions, and surface chemistry reactions on the dielectric nanochannel wall. The developed model is applicable to any level of the surface potential in the entire pH range in nanofluidic experiments.…”
Section: Introductionmentioning
confidence: 74%
“…2b). Such apparent reduction of S str implies that neglecting the electroviscous effect on the estimation of the streaming current in nanofluidics, usually assumed in the literatures [1,[8][9][10][11][12][13]18,19], is inappropriate and might result in an incorrect estimation for relevant ion transport phenomena. Fig.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations